2020
DOI: 10.1111/petr.13887
|View full text |Cite
|
Sign up to set email alerts
|

Do funding sources influence long‐term patient survival in pediatric liver transplantation?

Abstract: Background Socioeconomic status has been associated with inferior outcomes after multiple surgical procedures, but has not been well studied with respect to pediatric liver transplantation. This study evaluated the impact of insurance status (as a proxy for socioeconomic status) on patient and allograft survival in pediatric first‐time liver transplant recipients. Methods Our retrospective analysis of the UNOS data base from January 2002 through September 2017 revealed 6997 pediatric patients undergoing first‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Dick et al, using the UNOS database, found that children aged younger than 18 years with Medicaid insurance had a relative risk of 1.42 of posttransplant mortality, further demonstrating that socioeconomic position impacts transplant outcomes. [ 33 ]…”
Section: Socioeconomic Disparitiesmentioning
confidence: 99%
“…Dick et al, using the UNOS database, found that children aged younger than 18 years with Medicaid insurance had a relative risk of 1.42 of posttransplant mortality, further demonstrating that socioeconomic position impacts transplant outcomes. [ 33 ]…”
Section: Socioeconomic Disparitiesmentioning
confidence: 99%
“…21 However, as noted by Dick et al in similar work involving the pediatric liver transplant population, it is important to remember the limitations of healthcare systems in mitigating the social drivers of health, which require structural changes reliant on political advocacy, community organizing, and action (such as increasing minimum wage, access to affordable housing, access to education, etc). 22 Just as we and Medicaid expansion under the ACA, publicly insured KT recipients were significantly more likely to die than privately insured recipients (9.2% vs 4.0%, respectively; RR = 1.22, CI, 1.15-1.31). B, After the KAS revision and Medicaid expansion under the ACA, publicly insured KT recipients were significantly more likely to suffer allograft failure than privately insured recipients (5.8% vs 3.7%, respectively; RR = 1.10, CI, 1.03-1.29).…”
Section: Discussionmentioning
confidence: 99%
“…21 However, as noted by Dick et al in similar work involving the pediatric liver transplant population, it is important to remember the limitations of healthcare systems in mitigating the social drivers of health, which require structural changes reliant on political advocacy, community organizing, and action (such as increasing minimum wage, access to affordable housing, access to education, etc). 22 Just as we expect evidence-based treatments for individual diseases, we need evidence-based policies and solutions to systemic health inequities. Physician and patient voices, often via collective organizations, can be valuable and influential in this realm.…”
Section: Discussionmentioning
confidence: 99%
“…25 LDLT has recently been associated with an improved patient survival when compared with whole liver transplant 21 and is associated with a lower incidence of acute cellular rejection. 20 Patients who received an LDLT were more likely to have private insurance, 26 and patients with public insurance are almost twice as likely to die after a liver transplant. 27 Although it has been shown that all race and ethnic groups have comparable posttransplant outcomes, higher rates of death and graft loss, higher rates of wait list mortality, and a lesser likelihood of obtaining exception points have been noted in individuals with public insurance.…”
Section: Living Donor Liver Tr Ans Pl Antmentioning
confidence: 99%